The Representation of Mental Health Construct in Billie Eilish’s Song - Farah Dhiya Rofifah; Marsya Ariesta Cahyani; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research investigates how mental health concepts are depicted in the lyrics of selected songs by Billie Eilish. Although there is an increasing discourse surrounding mental health in modern popular music, there is a scarcity of literary hermeneutic analyses focusing on psychological representations within song lyrics. Employing a descriptive qualitative methodology framed by hermeneutics, this study scrutinizes five official tracks: Lovely, Everything I Wanted, Wildflower, TV, and idontwannabeyouanymore. Data were gathered using documentary methods from authenticated official lyric sources and were analyzed through meticulous close reading and contextual interpretation. The analysis is categorized into four distinct themes: implicit meanings, symbolic expressions, emotional undertones, and mental health challenges. The results indicate that the chosen lyrics consistently reflect mental health issues through motifs of anxiety, vulnerability, emotional suppression, loneliness, and internal strife. Symbolic imagery, including glass, water, fire, and physical sensations, is employed to illustrate psychological distress and emotional instability. Furthermore, the songs underscore emotional contradictions and a fluctuating self-image, portraying mental health as a multifaceted psychological condition. This research illustrates that symbolic imagery serves as a narrative mechanism that shapes psychological identity and emotional turmoil, suggesting that contemporary song lyrics can function as literary texts that articulate modern mental health narratives.